แนวทางการนิเทศการสอนครูไทยที่สอนภาษาจีนระดับมัธยมศึกษาของโรงเรียนสังกัดสำนักงานเขตพื้นที่การศึกษามัธยมศึกษาเขต 1 และเขต 2 กรุงเทพมหานคร - สุรเชษฐ์ อโลภะตานนท์ (จุฬาลงกรณ์มหาวิทยาลัย, 2020)
This study had 2 aims. 1) To study the current states and the expectations for instructional supervision of Thai teachers teaching Chinese language at secondary schools under the Secondary Educational Service Area Office 1 and 2 in Bangkok. 2) To propose instructional supervision guidelines for the development of Thai teachers who teach Chinese language at secondary schools under the Secondary Educational Service Area Office 1 and 2 in Bangkok.. The study was divided into 2 parts. Part 1 examined the current states and expectations for instructional supervision of Thai teachers teaching Chinese language at secondary schools. The population was 119 secondary schools under the Secondary Educational Service Area Office 1 and 2 in Bangkok (Academic Year 2019). There were 556 respondents including 199 Thai teachers who taught Chinese language, 119 assistant directors of Academic Administration Department, 119 heads of Foreign Language Department, and 119 heads of Supervision Department. A 5-point Likert scale questionnaire was used as the research instrument. Part 2 explored the instructional supervision guidelines for the development of Thai teachers who teach Chinese language at secondary schools. The data were collected through semi-structure interviews. The interviewees were from five schools of the top ten schools whose students had the highest average score in the national Chinese language proficiency test (PAT 7.4) for three consecutive years. There were 15 interviewees involving the school administrator, head of Foreign Language Department, and instructional supervisor of each selected school. The interview data were analyzed using content analysis. The results revealed that regarding the current states of instructional supervision of Thai teachers teaching Chinese language, the area with the highest average was the learning measurement and evaluation which was at a high level. Respecting the expectations for instructional supervision of Thai teachers who teach Chinese language, the areas with the highest average were the teaching materials and the learning measurement and evaluation which were at the highest level. The PNI results suggested that the area of learning activity management was the most needed. The guidelines for instructional supervision of Thai teachers who teach Chinese language at secondary schools under the Secondary Educational Service Area Office 1 and 2 in Bangkok including the aspect of curriculum, learning activity management, teaching material and learning measurement and evaluation.